2018
DOI: 10.12688/f1000research.12068.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in cancer outcomes in HIV-positive smokers

Abstract: HIV-infected smokers are at relatively higher risk of cancer than HIV-infected non-smokers. HIV weakens the immune system and renders infected individuals more vulnerable to the carcinogenic effects of smoking. HIV-infected smokers suffer more aggressive forms of cancers than do non-smokers because of the cumulative effects of the virus and cigarette smoke carcinogens. The major types of cancer observed in HIV-infected smokers are lung, head and neck, esophageal, anal, and cervical cancers. In this review, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The immunological responses in persons chronically exposed to smoke from cigarettes are characterized by protracted secretion of inflammatory factors and by accumulation of several leukocytes in lung tissue and production of pro-fibrotic mediators such as transforming growth factor (TGF)-β [2,3]. These inflammatory perturbations likely result in increased risk development of tobacco associated morbidity including several types of cancer [4], autoimmune disorders [5], chronic obstructive pulmonary diseases [6] and respiratory infections [7].…”
Section: Introductionmentioning
confidence: 99%
“…The immunological responses in persons chronically exposed to smoke from cigarettes are characterized by protracted secretion of inflammatory factors and by accumulation of several leukocytes in lung tissue and production of pro-fibrotic mediators such as transforming growth factor (TGF)-β [2,3]. These inflammatory perturbations likely result in increased risk development of tobacco associated morbidity including several types of cancer [4], autoimmune disorders [5], chronic obstructive pulmonary diseases [6] and respiratory infections [7].…”
Section: Introductionmentioning
confidence: 99%
“…Non-HIV specific risk factors for cancer are well described and include obesity as well as coinfections, that is oncogenic viruses such as human papilloma virus (HPV) and viral hepatitis [29], while chronic inflammation may also play a role [30,31]. Taken together, these findings could suggest that the association between smoking and cancer varies based on HIVrelated immune impairment and inflammation, which potentially increases the carcinogenic effects of smoking on PLWH [22,[32][33][34][35]. To date, there is no evidence to support this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco use, especially smoking, has been causatively linked to cervical and anal cancers. 26,27 A recent review of cancers in HIV-positive smokers reported a higher risk of cancer among HIV-infected individuals with smoking habit, the major cancers being lung, head, and neck, anal as well as cervical cancers. 26 In this study, we also found a significant association of tobacco use with anal HR-HPV infection as well as with concurrent cervical and anal HR-HPV infection among WLHIV.…”
Section: Concurrent Cervical and Anal Hr-hpv Infection In Wlhiv And H...mentioning
confidence: 99%